Antitumor and antioxidant activity of some metal complex compounds - Stefka Ivanova; Stefan Balkanski; Petar Atanasov; Maria Chaneva; Danka Obreshkova; Valentin Dimitrov; Krasimira Kazalukova; Lily Peikova; Ognian Markov (Pensoft Publishers, 2023)
In the last few years, interest in platinum drugs has increased. Successful treatment depends to a large extent on complex therapy and early diagnosis, which determines the great importance of knowledge of risk groups, clinical symptoms, and targeted use of diagnostic methods with biomarkers, biopsy and diagnostic imaging for early detection of the malignant process. Today, the mono-target strategy is being replaced by a poly-target therapy strategy, which achieves greater clinical efficacy in tumors with defined biomarkers. Key developments include elucidation of the mechanisms of tumor resistance to these drugs, the introduction of some new platinum- based agents and clinical combination studies using platinum drugs with resistance modulators or new drug-targeted drugs. Improved delivery of platinum drugs to tumors has been studied in early clinical trials using liposomal or copolymer-based products. Other investigated as anticancer agents are ruthenium and iron complexes. Ln(III) complexes have been shown to exert antioxidant activity.